Migrants’ Engagement with Space: A Comparative Analysis of Forced Migrants in Kolkata and Perth - Chakrabarti, Anuradha (Curtin University, 2022)
The research adopts an experimental comparative approach to compares the urban experience of forced migrants within a larger framework of politics of space in the two cities - Kolkata and Perth. The research provides new methodological, analytical and empirical insights into the process of migrants’ engagement with space. It adopts an etheno- phenomenology approach to collect data and puts the migrant, viewed both as a social and individual being, at the centre of its inquiry.